Updated distribution and range expansion of the gastropod invader melanoides tuberculata (Müller, 1774) in Brazilian waters - Coelho, Paula Nunes [UNESP]; Fernandez, Monica Ammon; Cesar, Daniela Aparecida Silveira [UNESP]; Ruocco, Ana Maria Cirino [UNESP]; Henry, Raoul [UNESP] (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2018)
Melanoides tuberculata (Müller, 1774), a mollusc native to the Afrotropical and Palearctic regions, has established populations in a number of localities in the Neotropical region. This non-native species was introduced to Brazil prior to 1970, but this record was only reported in the literature in 1986, and its invaded range has continued to expand. In this work, based on scientific literature and specimens deposited in biological collections, we provide an update on the distribution of M. tuberculata in Brazilian waters. Our results show that M. tuberculata currently occurs in 351 municipalities, 20 Brazilian States and the Federal District. We also provide a brief discussion about its potential as a vector for zoonotic diseases, and possible pathways for its introduction in Brazilian waters.
Keywords: Aquaculture; Fishkeeping; Invasive species; Neotropical region; Nonnative mollusc; Zoonotic potential